Effectiveness of low-crested (submerged) breakwater in wave attenuation - Mohd Ayub Mohd Yaakob, Mohd Ayub (2010)
Nowadays, submerged offshore breakwater has been constructed widely all over the world as one of the coastal protection scheme. The main purpose is to attenuate incoming wave and thus alter the wave condition on the lee side. This research deals with low crested (submerged) offshore breakwater. The objectives of this research are to find out the relationship between the variables of factors affecting wave attenuation and to produce a well research in producing an effective and optimum design of submerged offshore breakwaters. In this report, the author has outlined the methodology on how the research has been conducted in the laboratory followed by the analysis of the results and comparisons with the previous researchers. This research is focused mainly on two variables that affect the wave attenuation which are depth of submergence and crest width of the structure. The result shows that these two variables do have effect on the wave attenuation where their relationships are the wave attenuation is inversely proportional with the crest width while the wave attenuation is directly proportional with the relative crest elevation.